2020
DOI: 10.1152/ajpendo.00320.2019
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and estrogen regulate NALCN expression in human myometrial smooth muscle cells

Abstract: During pregnancy, the uterus transitions from a quiescent state to an excitable, highly contractile state to deliver the fetus. Two important contributors essential for this transition are hormones and ion channels, both of which modulate myometrial smooth muscle cell (MSMC) excitability. Recently, the sodium (Na+) leak channel, nonselective (NALCN), was shown to contribute to a Na+ leak current in human MSMCs, and mice lacking NALCN in the uterus had dysfunctional labor. Microarray data suggested that the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…suggesting that oxytocin has a sustained effect on the VDCC-dependent intracellular Ca 2+ concentration in MSMCs from pregnant rats (Arnaudeau, Lepretre, & Mironneau, 1994). We also recently demonstrated that NALCN expression and activity are regulated by the hormones progesterone and estrogen (Amazu et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…suggesting that oxytocin has a sustained effect on the VDCC-dependent intracellular Ca 2+ concentration in MSMCs from pregnant rats (Arnaudeau, Lepretre, & Mironneau, 1994). We also recently demonstrated that NALCN expression and activity are regulated by the hormones progesterone and estrogen (Amazu et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
“…*P<0.05, ** P<0.01, and *** P<0.001 by (D, E) unpaired t-test or (G,H) paired t-test. During the quiescent state, progesterone binding to the progesterone receptor (PR A/B ) increases NALCN expression and activity (Amazu et al, 2020). Sodium current through NALCN activates SLO2.1 channels, increasing K + efflux to maintain the cell in a hyperpolarized state.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…These results were in line with data published by Arnaudeau et al., suggesting that oxytocin has a sustained effect on the VDCC-dependent intracellular Ca 2+ concentration in MSMCs from pregnant rats ( Arnaudeau et al., 1994 ). We also recently demonstrated that NALCN expression and activity are regulated by the hormones progesterone and estrogen ( Amazu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, differential enrichment of transcription factor motifs suggests the involvement of cofactors that regulate transcriptional activation or repression depending on the cell type or environmental context. These cofactors may determine E2 regulation in the cortex and muscle, respectively, of Bcas1 , required for myelination, and the sodium leak channel, Nalcn ( Humphreys et al, 2014 ; Amazu et al, 2020 ). Interestingly, treatment induced CpG hypomethylation of hormone response genes, limited to young and middle-age animals, mainly occurred at intergenic regions or within introns ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%